Molecular complexes in earth’s planetary, cometary, and interstellar atmospheres (World Scientific, 1998)
This work introduces systematically the concept of weakly-bound complexes into the broad field of atmospheric sciences. to fill up the gap between our rapidly expanding knowledge of the individual properties of Van der Waals and hydrogen-bonded molecules, and our understanding of their role in the atmospheric processes, an ensemble of related topics are covered by a team of expert co-authors. The general properties of the weakly bound molecular complexes (or clusters) are discussed, as well as their distribution in the planetary atmospheres. Collision-induced and dimeric absorption and emission are considered in the context of atmospheric spectroscopy. The advanced experimental techniques which enables us to study the spectroscopic features of molecular complexes in the gas phase, or which are adsorbed, are reviewed. The role of molecular complexes in the cometary atmosphere, the Earth mesosphere, and the atmospheres of the giant planets and some of their satellites are also discussed in detail.